2021
DOI: 10.1175/bams-d-20-0178.1
|View full text |Cite
|
Sign up to set email alerts
|

Where Are the Most Extraordinary Lightning Megaflashes in the Americas?

Abstract: Capsule Summary NOAA’s Geostationary Lightning Mapper routinely observes extraordinary lightning “megaflashes” that exceed the extent and duration records from ground-based measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The PDD’s maximum trigger rate is perhaps its greatest limitation because it biases these statistics toward early optical pulses in long‐lived flashes. Most flashes that only last a fraction of a second will not be impacted, but the later emissions from flashes that develop over substantial horizontal distances and long durations (Peterson, 2021b; Peterson & Stano, 2021; Peterson, Rudlosky, & Deierling, 2017; M. J. Peterson et al., 2022) will not be represented. Otherwise, the PDD is a capable instrument that resolves lightning emissions over multiple orders of magnitude in irradiance (Kirkland et al., 2001) including radiant strokes with high peak currents, and dim optical pulses from in‐cloud processes (or strokes that have been severely attenuated by scattering in the cloud medium).…”
Section: Resultsmentioning
confidence: 99%
“…The PDD’s maximum trigger rate is perhaps its greatest limitation because it biases these statistics toward early optical pulses in long‐lived flashes. Most flashes that only last a fraction of a second will not be impacted, but the later emissions from flashes that develop over substantial horizontal distances and long durations (Peterson, 2021b; Peterson & Stano, 2021; Peterson, Rudlosky, & Deierling, 2017; M. J. Peterson et al., 2022) will not be represented. Otherwise, the PDD is a capable instrument that resolves lightning emissions over multiple orders of magnitude in irradiance (Kirkland et al., 2001) including radiant strokes with high peak currents, and dim optical pulses from in‐cloud processes (or strokes that have been severely attenuated by scattering in the cloud medium).…”
Section: Resultsmentioning
confidence: 99%
“…The impulsive VHF sources that we could identify were clustered in a single vertical layer between 4 and 8 km altitude (Peterson et al., 2021a). While megaflashes occur in many regions, the La Plata basin is one of the primary Americas hotspots (Peterson, 2021; Peterson & Stano, 2021)—along with the Continental United States, which also has an increased share of low‐altitude sources in Figure 6a. We have also recorded long horizontal lightning over the Mediterranean Sea (Peterson, Rudlosky, & Deierling, 2017) (Figure 6b) and showed that the other midlatitude oceanic regions with increased low‐altitude source fractions in Figure 6 are locations with long horizontal flashes (Figure 5 in Peterson, Deierling, et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…When a flash is terminated for violating one of these thresholds, it will be marked with a “degraded” quality flag in the operational GLM data and any subsequent events/groups will define a new and independent flash feature. This causes cases of long horizontal lightning megaflashes (Lyons et al., 2020; Peterson, 2021a; Peterson, Lang, et al., 2020) to be split into multiple (often tens of) “flash” features in the GLM LCFA data with all but the final emissions along each branch being designated as degraded quality.…”
Section: Methodsmentioning
confidence: 99%